Daily Habits and Energy Consumption: Go to Bed Earlier for Environmental Protection - Matsumoto, Shigeru (European Journal of Sustainable Development, 2019)
Energy consumption reduction in the residential sector is crucial for mitigating global warming. This has prompted researchers to investigate the determinants of household energy consumption from various aspects. However, previous studies have not examined the impact of time allocation on energy consumption, primarily because of the lack of surveys that simultaneously examine time allocation and energy consumption. We conducted an original survey of 547 Japanese households to examine whether time allocation affects their electricity consumption. We divided a 48-hour period into 192 time slots and asked the households to choose one of the 20 types of actions listed for each slot. We also collected information on the socioeconomic background and electricity consumption of the households. After controlling for various factors that affect household electricity consumption, we examined whether time allocation determines electricity consumption. The empirical result of our study revealed that while a married male’s bedtime does not affect electricity consumption, a married female’s bedtime does. This suggests that it is essential to understand the daily habits of consumers for proposing effective energy conservation measures. Keywords: Electricity Usage, Household, Time Allocation